2016
DOI: 10.14203/stipm.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of Evidence-Based Energy Policy-making: Government Regulation on Targeting Renewable Energy in Indonesia

Abstract: <p>The paper is based on research identifying lessons and approaches in making energy policy and scrutinizes whether empirical evidence–based energy policy exists in Indonesia. Empirical evidence–based energy policy has the potential to reduce poverty as well as have a greater impact on the economic performance of individuals, communities and the government. In this study, we used document analysis and key informant interviews to explore empirical evidence input in energy policy-making. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Formulation of Indonesia national strategic policy of science and technology development Policy contents as described above indicate that the substance through the Indonesia national strategic policy of science and technology development present certain drawback due to weak problem identification and insufficient support of empirical data. To confirm such findings, the proposed policy formulation process is compulsory to be disclosed, supported by prior relevant research results (Hermawati et al, 2016;Zhang et al, 2018).…”
Section: Jstpm 123mentioning
confidence: 88%
“…Formulation of Indonesia national strategic policy of science and technology development Policy contents as described above indicate that the substance through the Indonesia national strategic policy of science and technology development present certain drawback due to weak problem identification and insufficient support of empirical data. To confirm such findings, the proposed policy formulation process is compulsory to be disclosed, supported by prior relevant research results (Hermawati et al, 2016;Zhang et al, 2018).…”
Section: Jstpm 123mentioning
confidence: 88%
“…Meanwhile, the elasticity value of household electricity consumption to GDP growth is <1 in the short and long term. This indicated that electricity consumption in the household sector is not responsive to changes in GDP growth both in the short and long term (Hermawati et al, 2016).…”
Section: Household Sectormentioning
confidence: 95%
“…Changes to government revenues have little impact on fuel subsidy spending in the short and long term (Tubbs, 2012;Hermawati et al, 2016), whereas the change in the total final consumption of BBM has a major impact on fuel subsidy spending in the short and long term.…”
Section: Output In Economy Indonesiamentioning
confidence: 99%
See 1 more Smart Citation